The Economics of the Joint Management of Water Resources and Aquatic Species in the United States. (26th July 2020) - Kroetz, Kailin; Kuwayama, Yusuke; Vexler, Caroline
Abstract: The health of many marine, coastal, freshwater, and other aquatic ecosystems is inextricably linked to decisions about the management of water quality and quantity. In this article we review the economic literature aimed at quantifying the impacts of water resource management on aquatic species in the United States and the potential welfare gains of managing water and aquatic species systems jointly. Existing studies consider multiple water uses, such as agricultural irrigation and hydropower generation, as well as different societal benefits from aquatic species, such as commercial and recreational fishing and endangered species preservation. These studies use a variety of methodologies, including stated and revealed preference techniques, bioeconomic modeling, and reduced-form econometrics. We conclude with a discussion of future directions for research that could increase understanding of the trade-offs between water and aquatic species management outcomes and identify gains from the joint management of water resources and aquatic species in the United States.